2016
DOI: 10.1152/ajpendo.00479.2015
|View full text |Cite
|
Sign up to set email alerts
|

Pulsatile delivery of a leucine supplement during long-term continuous enteral feeding enhances lean growth in term neonatal pigs

Abstract: TA. Pulsatile delivery of a leucine supplement during long-term continuous enteral feeding enhances lean growth in term neonatal pigs. Am J Physiol Endocrinol Metab 310: E699 -E713, 2016. First published February 16, 2016 doi:10.1152/ajpendo.00479.2015.-Neonatal pigs are used as a model to study and optimize the clinical treatment of infants who are unable to maintain oral feeding. Using this model, we have shown previously that pulsatile administration of leucine during continuous feeding over 24 h via oroga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 92 publications
(120 reference statements)
4
20
1
Order By: Relevance
“…Supplementation of leucine stimulated post‐absorptive protein synthesis by activating the mTOR pathway, which is consistent with our hypothesis and past studies (Boutry et al, ; Suryawan et al, ). The increase in protein synthesis of LD muscle was mediated by an increase in translation initiation, as indicated by an increased activation of the translation initiation factors, 4E‐BP1 and S6K1 (Wilson et al, ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Supplementation of leucine stimulated post‐absorptive protein synthesis by activating the mTOR pathway, which is consistent with our hypothesis and past studies (Boutry et al, ; Suryawan et al, ). The increase in protein synthesis of LD muscle was mediated by an increase in translation initiation, as indicated by an increased activation of the translation initiation factors, 4E‐BP1 and S6K1 (Wilson et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…These results indicate that protein degradation in the skeletal muscle remained unchanged in response to leucine supplementation, resulting in a similar amount of EAAs releasing into the metabolic pool; however, the increase of serum EAAs by leucine may have been resulted from a reduction of the loss of EAAs from the metabolic pool, probably by inhibited oxidation of EAAs (Holecek et al, 2016) and then increased the concentrations of EAAs in LEU (Dijk et al, 2018). In addition, previous researches also showed that supplementation of leucine can increase AA utilization (Boutry et al, 2016;Rudar et al, 2016). It can be seen that leucine supplementation can increase the utilization efficiency of EAAs and provide sufficient substrates for protein synthesis in post-absorptive state.…”
Section: Discussionmentioning
confidence: 96%
“…However, the switch to oral feedings is limited by the concern of the infant´s ability to metabolize the nutrients offered and the risk of developing feeding-related pathologies (Berseth 2005) which often leads to dietary protein intakes that cannot support maximal growth (Embleton et al 2001; Rigo et al 2002). Using the neonatal pig as a model, our laboratory has demonstrated a dual effect of dietary Leu in promoting muscle protein accretion in newborns, by acting as an essential AA (EAA) in protein synthesis and also by modulating the intracellular signaling pathways that regulate translation initiation (Torrazza et al 2010; Suryawan et al 2012; Columbus et al, 2015; Boutry et al, 2016). Given that the clinical condition of LBW infants often precludes their consumption of full feeds over protracted lengths of time, in the present study we assessed the potential for using oral Leu supplementation alone, or in combination with Ile and Val, to enhance the lean growth of neonatal pigs when both protein and energy intakes are supotimal for an extended period.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we showed that both oral and parenteral administration of Leu to neonatal pigs enhances muscle protein synthesis in the short-term by increasing the phosphorylation of the mechanistic target of rapamycin complex 1 (mTORC1) and its downstream effectors, namely ribosomal protein S6 kinase 1 (S6K1) and eukaryotic initiation factor 4 (eIF4)-binding protein 1 (4EBP1; Escobar et al 2005; Wilson et al 2010; Torrazza et al 2010; Suryawan et al 2012; Figure 1). Further, when a Leu supplement was delivered as a pulse to an otherwise complete diet over a more extended period, rates of protein synthesis and lean mass accretion were increased (Boutry et al 2016). Nonetheless, Leu supplementation did not improve muscle growth in neonatal pigs when energy and protein (Manjarin et al, 2016) intakes were restricted, despite an increase in mTOR pathway activation.…”
Section: Introductionmentioning
confidence: 99%
“…Much attention has recently been directed to studying Leu signaling in animal nutrition. For example, pulsatile delivery of Leu to neonatal pigs fed a milk replacer orogastrically increases lean growth by 25% (Boutry et al, 2016), likely due to insulin-stimulated translation initiation (Davis et al, 2015). Wilson et al (2009) demonstrated that ingestion of a meal providing one-sixth of the daily dietary Leu requirements provoked the most rapid stimulation of muscle protein synthesis with highly efficient peak activation within 30 min.…”
Section: Functional Amino Acids and Feeding Strategiesmentioning
confidence: 99%